Clinical outcomes of 168 Chinese patients after local surgery for bone metastases arising from advanced renal cell carcinoma. (15th April 2020) - Dong, Yi; Wang, Zheng; Lu, Xin; Wu, Zhenjie; Zhang, Zongqin; Yu, Yongwei; Peng, Fei; Liu, Bing; Wang, Linhui
Abstract : Background: The effectiveness of local surgery for bone metastases (BM) arising from renal cell carcinoma (RCC) remains uncertain. Herein, the authors performed what to the best of their knowledge is the first investigation of the outcomes of Chinese patients with RCC and BM. Methods: Data were collected for 168 patients with RCC and BM who were treated at Changzheng Hospital in Shanghai, China, between March 2009 and December 2018. All patients underwent local surgery for BM arising from RCC. Overall survival (OS) was defined as the interval between the date of local surgery and death or last follow‐up and was estimated using the Kaplan‐Meier method. Univariate and multivariable Cox proportional hazards analyses were used to identify significant prognostic factors. Results: The median OS in the study cohort was 43 months (range, 0‐113 months). The 1‐year, 3‐year, and 5‐year survival rates after surgery were 77.4%, 55.9%, and 31.8%, respectively. Univariate analyses demonstrated significant survival differences associated with sex ( P = .003), the number of preoperative metastatic sites (BM alone or BM with concomitant metastasis; P < .001), and the number of BM (single or multiple; P = .008). OS also did not appear to differ regardless of whether the patients received postsurgical targeted therapy. Multivariable Cox regression demonstrated that the following characteristics were independent predictors of OS: the number of preoperative metastatic sites, International Metastatic Renal Cell Carcinoma Database Consortium risk score, and Memorial Sloan Kettering Cancer Center score. Conclusions: Careful patient selection for local surgery is of paramount importance. The prognoses of patients in the Memorial Sloan Kettering Cancer Center–based and International Metastatic Renal Cell Carcinoma Database Consortium–based poor‐risk groups were much worse than those of the intermediate‐risk groups. In current clinical practice, "stratified treatment" can be performed according to these criteria. Abstract : The effectiveness of local surgery for bone metastases (BM) arising from renal cell carcinoma (RCC) remains uncertain. In what to their knowledge is the first prognostic study of Chinese patients undergoing local surgery for BM arising from RCC, the authors report that the number of metastatic sites, International Metastatic Renal Cell Carcinoma Database Consortium risk score, and Memorial Sloan Kettering Cancer Center score are significant and independent predictors of postsurgical overall survival.